Factors enhancing economic performance in hospitality. The paradigm of Greek hotel companies / S.T. Kapiki - Kapiki, S.T (Universiti Teknologi MARA (UiTM), Malaysia, 2012)
Hotel managers focus on identifying, creating or developing competitive advantages that can be utilised in order to improve the company's economic performance and bottom line. This paper attempts to identify those internal factors having enhanced the financial performance in the Greek hospitality sector during 2008- 2010. The survey was conducted in Greek high-class hotel companies and reveals that the enhancement of a hotel's economic performance can be achieved by the following key factors: exceptional services; well-trained and highly motivated associates; contemporary managerial approaches; pricing tactics maximising the revenue per room; investments in new technology systems; organization of activities keeping the guests (and the revenues) within the premises; application of sustainable practices; niche marketing and advertising so as to attract new guests; and, formal cooperation with other tourism stakeholders. The findings of this study are suggested as best practices for the hospitality industry.